2014
DOI: 10.1111/1462-2920.12404
|View full text |Cite
|
Sign up to set email alerts
|

Pathway of nitrous oxide consumption in isolated Pseudomonas stutzeri strains under anoxic and oxic conditions

Abstract: The microbial consumption of nitrous oxide (N2O) has gained great interest since it was revealed that this process could mitigate the greenhouse effect of N2O. The consumption of N2O results from its reduction to dinitrogen gas (N2) as part of the denitrification process. However, there is ongoing debate regarding an alternative pathway, namely reduction of N2O to NH4(+), or assimilatory N2O consumption. To date, this pathway is poorly investigated and lacks unambiguous evidence. Enrichment of denitrifying act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 43 publications
2
31
0
Order By: Relevance
“…However, it has been recently demonstrated the capacity of Ps. stutzeri species to consume N 2 O under oxic conditions (Desloover et al, 2014), supporting previous observations showing that the nosZ gene can also be expressed at high O 2 concentrations (Miyahara et al, 2010). Supporting these findings, it has been recently reported in Pa. denitrificans the reduction of N 2 O at high O 2 partial pressure (Qu, Bakken, Molstad, Frostegard, & Bergaust, 2016).…”
Section: Regulatorssupporting
confidence: 85%
See 1 more Smart Citation
“…However, it has been recently demonstrated the capacity of Ps. stutzeri species to consume N 2 O under oxic conditions (Desloover et al, 2014), supporting previous observations showing that the nosZ gene can also be expressed at high O 2 concentrations (Miyahara et al, 2010). Supporting these findings, it has been recently reported in Pa. denitrificans the reduction of N 2 O at high O 2 partial pressure (Qu, Bakken, Molstad, Frostegard, & Bergaust, 2016).…”
Section: Regulatorssupporting
confidence: 85%
“…Recent isotope tracing experiments by using Ps. stutzeri showed that consumption of N 2 O via assimilatory reduction to ammonium did not occur (Desloover et al, 2014). However, the latter studies showed that respiratory N 2 O reduction can be coupled to N 2 fixation as N 2 O is first reduced to N 2 before is further reduced to ammonium and incorporated into cellular biomass.…”
Section: N 2 O Metabolism In Denitrifying Bacteriamentioning
confidence: 99%
“…This result was consistent with a previous report (Poulsen et al, 2014). The genera Pseudomonas and Stenotrophomonas belonging to Gamma-proteobacteria were ubiquitous in sediment and waste plants, while not detected in the gut due to primer partial (Cutruzzola et al, 2003;Bartacek et al, 2010;Bellini et al, 2013;Desloover et al, 2014;Zheng et al, 2014). The community composition of nitrite-and nitrous-oxide-reducing bacteria in the gut was indeed affected by the presence of cyanobacteria.…”
Section: Discussionsupporting
confidence: 92%
“…55 % was achieved with such inoculation. Desloover et al (2014) identified a Pseudomonas stutzeri strain that was able to grow on N 2 O as the only source of N and electron acceptor. Pseudomonas stutzeri is known to possess both nitrogenase and nitrous oxide reductase (nosZ I) (Pomowski et al, 2011).…”
Section: Nitrous Oxide Consumptionmentioning
confidence: 99%
“…Pseudomonas stutzeri is known to possess both nitrogenase and nitrous oxide reductase (nosZ I) (Pomowski et al, 2011). A 15 N labelling study showed that N 2 O is immobilized into microbial biomass via N 2 O reduction to N 2 followed by reuptake of the released N 2 and subsequent fixation into NH + 4 via nitrogenase (Desloover et al, 2014). …”
Section: Nitrous Oxide Consumptionmentioning
confidence: 99%